Penerapan Game Edukasi science Quest 3 Dunia untuk Siswa SDI Ende 14: Penelitian - Felmy Ariyanty Bouk; Elsiana Deno Kolly; Nining Sar’iyyah; Maria Dima Mbere; Agustina Pali; Agnes Demi Rando (Jurnal Pengabdian Masyarakat dan Riset Pendidikan, 2026)
This activity aimed to implement the educational game Science Quest 3 Dunia as a science learning medium to enhance students’ learning interest and understanding of science concepts at SDI Ende 14. The participants were students of SDI Ende 14. The activity was conducted at SDI Ende 14, Ende Regency. The method used was game-based learning, which began with preparation and an introduction to science materials, followed by the guided use of the Science Quest 3 Dunia educational game, student assistance during the gameplay process, and discussion and evaluation of learning outcomes. Through the implementation of this educational game, students demonstrated higher enthusiasm and active participation in science learning, as well as improved understanding of the material compared to conventional learning methods.